Effect Of Knowledge, Attitude, Role Of Health Officers And Family Support On Early Detection Of Pregnancy Signs With The Quality Of Utilization Of The Mch Handbook In The Puskesma Region Kesamben Jombang Regency - sari, wahyu anjas; Sari, Nia; Suhita, Byba Melda (Journal of Global Research in Public Health, 2019)
Indirect factors of maternal death are late knowing the danger signs of pregnancy. In recognizing complications of pregnancy is the use of KIA books. The purpose of the study was to analyze the effect of knowledge, attitudes, the role of health workers and family support on early detection of pregnancy danger signs on the quality of utilization of MCH books in the Kesamben District Health Center in Jombang Regency. The design of the study is quantitative with a cross sectional approach. The study was conducted in December 2018 with a population of 564 and samples of 234 pregnant women with a claster sample random sampling technique. Data collection of independent and dependent variables with questionnaire instruments and processed using editing, coding, scoring and tabulating and tested with Ordinal Regression test. The results of the ordinal regression statistical test found that there was an effect of knowledge, attitudes, roles of officers and family support on the quality of utilization of MCH books with a fourth variable significance value <0.05. Family support has the highest wald value so that it has a more dominant influence on the quality of the utilization of MCH books. It was concluded that with family support variables as the dominant variable. This research is expected that pregnant women seek information related to pregnancy so that they can prepare for delivery safely and comfortably.